Adaptive powerline interference cancellation in electrocardiography - Tarroza, Antonio Ernesto R. (1993)
Powerline interference, which is of common-mode, causes distortion in electrocardiograph (ECG) readings. There have been several attempts at removing noise in ECG readings. One of which is through digital signal processing. This thesis aims to study fixed or non-adaptive and adaptive digital filter theories and their application to powerline noise cancellation in ECG signals. The performance of fixed and adaptive filters were studied and compared with one another based on a common set of parameters. Both fixed and adaptive filter employed the Least Mean Square (LMS) algorithm applied to both transversal and lattice structures. Studies revealed that although the lattice structure holds promise in filtering out powerline noise, the fixed and adaptive LMS transversal filters still enjoyed superior performance over that of their lattice counterparts.